General Practitioners' Perception of Risk for Travelers Visiting Friends and Relatives. Issue 6 (15th July 2015) - Heywood, Anita E.; Forssman, Bradley L.; Seale, Holly; MacIntyre, C. Raina; Zwar, Nicholas
Abstract : Background: General practitioners (GPs) are an important source of pre‐travel health advice for travelers; however, only a few studies have investigated primary healthcare provider–related barriers to the provision of pre‐travel health advice, particularly to travelers visiting friends and relatives (VFR). We aimed to investigate Australian GPs' knowledge, attitudes, and practices with regard to VFR travelers. Methods: A postal survey was sent to randomly sampled GPs in Sydney, Australia, in 2012. The questionnaire investigated GPs' perception of risk and barriers to the provision of advice to VFR travelers. Results: Of 563 GPs, 431 (76.6%) spoke a language other than English (LOTE) with 361 (64.1%) consulting in a LOTE. Overall, 222 (39.4%) GPs considered VFR travelers to be at higher risk than holiday travelers, with GPs consulting in English only [adjusted odds ratio (aOR) 1.65, 95% confidence interval (CI) 1.11–2.44, p = 0.01] and GPs considering long‐term migrants as VFR travelers (aOR 1.86 95% CI 1.07–3.23, p = 0.03) remaining significant on multivariate analysis. Conclusions: Multilingual GPs are a valuable resource to reducing language and cultural barriers to healthcare. Targeted education of this subgroup of GPs may assist in promoting pre‐travel health assessments for VFR travelers. Awareness of the need for opportunistic targeting of migrants for pre‐travel consultation through routine identification of future travel is needed.